2007
DOI: 10.1073/pnas.0611079104
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of progressive renal injury by genetic manipulation of Klotho gene

Abstract: Klotho, an antiaging gene with restricted organ distribution, is mainly expressed in the kidney tubules; the mutant mice have shortened life span, arteriosclerosis, anemia, and osteoporesis, features common to patients with chronic renal failure. Conceivably, the reduction of the Klotho gene expression may contribute to the development of kidney failure; alternatively, its overexpression may lead to the amelioration of renal injury in an ICR-derived glomerulonephritis (ICGN) mouse model with subtle immune comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
212
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(231 citation statements)
references
References 33 publications
(36 reference statements)
4
212
1
5
Order By: Relevance
“…However we can speculate on a nephroprotective role of Klotho based on the beneficial effect of Klotho overexpression on progressive renal injury 55 and in AKI. 42,56 In summary, the inflammatory cytokines TWEAK and TNF␣ downregulate Klotho in renal tubular cells through an NFBdependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However we can speculate on a nephroprotective role of Klotho based on the beneficial effect of Klotho overexpression on progressive renal injury 55 and in AKI. 42,56 In summary, the inflammatory cytokines TWEAK and TNF␣ downregulate Klotho in renal tubular cells through an NFBdependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Locally, a reduction of Klotho expression contributed to progression of kidney failure; although its overexpression ameliorated renal injury in a mouse model. 46 Ad-Klotho gene transfer improved serum creatinine and reduced renal apoptosis induced by ischemia-reperfusion in rats. 22 Klotho transfection reduced H 2 O 2 -induced tubular cell apoptosis in culture.…”
Section: Discussionmentioning
confidence: 99%
“…aKlotho is found in urine and serum of rodents and humans 2,20,42,56 ; and the kidney has the highest abundance of aKlotho compared with other organs. Clinical and experimental animal studies showed low renal tubular aKlotho expression in both acute kidney injury and CKD 10,40,42,43,[56][57][58][59][60][61][62] and low circulating aKlotho levels in kidney diseases of a variety of etiologies in animals 42,43,56,62 and humans. 32,44,61,63 These data suggest that the kidney contributes to circulating aKlotho.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that plasma and urine levels of soluble Klotho are significantly elevated in DM patients with relatively preserved renal function compared to control subjects. Hence, in DN, Klotho expression levels were decreased in kidneys of patients with early DN but with increased levels of plasma and urinary Klotho, and that Klotho deficiency may serve as a biomarker as well as a pathogenic factor for the progression of renal disease and further complications [39][40][41].…”
Section: Klotho-vitamin D-vdr Axismentioning
confidence: 99%